MEASUREMENTS OF HAPPINESS AT THE UNIVERSITY IN THE CONTEXT OF THE ECONOMY OF HAPPINESS - Ноздріна, Лариса; Жеребило , Ірина; Волошок , Олена (Socio-economic relations in the digital society, 2020)
The article describes theoretical, methodological approaches to defining and measuring the economy of happiness. The theoretical basis of the economy of happiness involves the study of economic and other factors that determine human happiness, its dependence on the level of economic development of the country and determine the parameters for assessing the level of happiness of society as a whole. The «Easterlin paradox» is highlighted, which notes the limited impact of economic growth on the level of happiness of citizens. The economy of happiness at the macro level is due to happiness at the micro level, in our study - at the University. Its purpose was to determine the level and measure the factors of happiness, and their impact, taking into account modern network communications on the productivity and creativity of students and teachers. The article presents the results of a study of 323 students and teachers of various higher education institutions of Ukraine, interviewed using a cloud questionary created using Google Form. The results of the study showed that most students and teachers are satisfied with life in higher education, believe that the factors of happiness are material, spiritual and social benefits together. It has been proven that young people are generally happier than older people rate, their level of happiness in terms of their role at the University at 4 (on a 5-point scale). It is shown that almost half of the respondents use their time irrationally on the Internet, but they are satisfied with it; most of the respondents would feel happier if they used their time as productively as possible and had the opportunity to spend more time on self-development and creativity.